Characterization of a YAC contig spanning the pseudoautosomal region - Ried, Karin; Mertz, Annelyse; Nagaraja, Ramaiah; Trusgnich, Michelle; Riley, John H.; Anand, Rakesh; Lehrach, Hans; Page, David; Ellison, Jay W.; Rappold, Gudrun (Genomics, 1995)
Due to its unique biology of partial sex linkage and high recombination rates, the pseudoautosomal region (PAR1) on both X and Y chromosomes has attracted considerable interest. In addition, an extremely high level of YAC instability has been observed in this region. We have derived 82 YAC clones from six different YAC libraries mapping to this 2.6-Mb region. Of these a subset of 22 YACs was analyzed in detail. YAC contigs were assembled using 67 pseudoautosomal probes, of which 64 were unambiguously ordered. All markers are well distributed over the entire region, including the middle part of the region, which has previously been found difficult to contig. Two gaps of less than 50 kb within the genomic locus of CSF2RA and around XE7 remain, which could not be covered with YACs, cosmids, or phages. This YAC contig anchored on the physical map of PAR1 represents one of the best characterized large regions of the human genome with a map completion greater than 90% at 100-kb resolution and has permitted the accurate localization of all known genes within this region.
Online 25 May 2002
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 31.03.2021